2009
DOI: 10.1007/s12016-009-8178-2
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptors in Pregnancy Disorders and Placental Dysfunction

Abstract: The Toll receptor was originally identified as a regulator of embryogenesis in Drosophila. Toll-like receptors (TLRs) in mammals recognize infectious agents and other danger signals. Activation of TLRs on trophoblast influences immune cell recruitment, cytokine secretion, and decidual responses to invading pathogens during pregnancy. Importantly, biological effects of TLR signal transduction at multiple maternal-fetal interfaces may contribute to several pregnancy pathologies associated with placental dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 103 publications
0
79
0
Order By: Relevance
“…4). In the downstream of TLRs, signal molecules involved in Myd88-dependent orindependent pathways regulate transcriptional factors such as nuclear factor-kB (NFkB) and activator protein 1 (AP1), leading to the initiation of transcription in the nucleus (Riley & Nelson 2010). The release of human b-defensin (hBD) 2 was found to be controlled by phosphoinositide 3 kinase (PI3K) and NFkB, whereas The values with different letters are significantly different (P!0.05).…”
Section: Discussionmentioning
confidence: 99%
“…4). In the downstream of TLRs, signal molecules involved in Myd88-dependent orindependent pathways regulate transcriptional factors such as nuclear factor-kB (NFkB) and activator protein 1 (AP1), leading to the initiation of transcription in the nucleus (Riley & Nelson 2010). The release of human b-defensin (hBD) 2 was found to be controlled by phosphoinositide 3 kinase (PI3K) and NFkB, whereas The values with different letters are significantly different (P!0.05).…”
Section: Discussionmentioning
confidence: 99%
“…TLR-dependent innate immunity plays a role as the first line of host defense. Activation of TLRs on trophoblast cells influences immune cell recruitment, proinflammatory cytokine secretion, and decidual responses to invading pathogens during pregnancy [48]. Importantly, recent data directly implicate signaling by TLRs at multiple maternal-fetal interfaces in the pathogenesis of several pregnancy pathologies, including preeclampsia, intrauterine growth restriction, and preterm labor [48].…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%
“…Recently, increasing numbers of studies have demonstrated that TLR2 and TLR4 are involved in the development of the host innate inflammatory response in I/R-induced pathology, very likely through their interaction with endogenous agonists (Arumugam et al 2009). TLR4 (which can bind bacterial lipopolysaccharide (LPS)) is widely expressed in the placenta (Riley & Nelson 2010), uterus, and cervix (Gonzalez et al 2007) and its expression is upregulated during gestation.…”
Section: Introductionmentioning
confidence: 99%